Odpowiedzi

Najlepsza Odpowiedź!
2009-11-11T14:12:52+01:00
1) 8x+4=36
2) 3(1-x)-(1-2x)=9
3) 12x-(x+5)=10x-1
4) 3(2x-4)=2x+8
5) 4(x+2)-7(2x-1)+9(3x-4)=30
6)(x+1)²=(x-1)²-2(x-4)

1)
8x = 36-4
8x = 32
x = 4

2)
3-3x - 1 + 2x = 9
-x = 9-2
x = -7

3)
12x - x - 5 = 10x - 1
11x - 10x = -1 + 5
x = 4

4)
6x-12 = 2x + 8
6x - 2x = 8 + 12
4x = 20
x = 5

5)
4x + 8 - 14x + 7 + 27x - 36 = 30
4x - 14x + 27x = 30 - 15 + 36
17x = 51
x = 3

6)
x²+2x+1=x²-2x+1 - 2x + 8
2x+2x+2x = 1+8-1
6x = 8
x = 8/6
x = 4/3
2009-11-11T14:18:05+01:00
1) 8x + 4 = 36/-4
8x = 36-4
8x=32/:8
x=4

2)3(1-x)-(1-2x)=9
3-3x-1+2x=9 /-3 ; +1
-3x + 2x = 9-3+1
-x = 7 /*(-1)
x = -7

3) 12x - (x+5)= 10x-1
12 x - x - 5 = 10x-1/-10x ; +5
12x-x-10x = -1+5
x = 4

4) 6x - 12 = 2x+8 / -2x; +12
4x = 20 /:4
x = 5

5) 4x + 8 - 14x+ 7 + 27x - 36 =30
17x = 51 / :17
x = 3